Pengingat Pemberantasan Sarang Nyamuk (PSN) berbasis android dalam upaya pembudayaan PSN pada masyarakat - Emilia Chandra; Bambang Ariyadi; Zunidra Zunidra (Riset Informasi Kesehatan, 2022)
Background : The eradication of mosquito nests (PSN) has not become a culture in the community, even though the government has established a one-house program for larva monitoring (Jumantik), the community has not yet had a strong motivation to implement PSN in their environment and house. Therefore, the researchers made a reminder application in the form of an alarm that will sound once a week to remind the housewives. The problem in this research is how effective is the application of the mosquito nest eradication reminder (PSN) in an effort to cultivate the 3M PLUS PSN in the community.(Objective) The purpose of this study is to analyze the cultural mean of the 3M PLUS PSN reminder in families who are given the PSN reminder application, to analyze the cultural retention of the 3M PLUS PSN leaflet and to analyze the effectiveness of the PSN reminder application by providing 3M PLUS PSN leaflets in an effort to cultivate PSN 3M PLUS in the community Method : This study used a quasi experimental research design with a posttest design with a control group (posttest) only control group design. The study design was used to measure the results of the intervention in both groups, namely to measure whether the PSN reminder application was effective in measuring the 3M Plus PSN culture. The intervention group received a PSN reminder application and the control group was given leaflets. The intervention group and the control group were both measured after receiving treatment at the time of the study. Results : Based on the results of the study, it was shown that the housewives who were given the PSN reminder application intervention were cultured to carry out Mosquito Nest Eradication activities and 3M Plus in their homes and neighborhoods. The culture of the house jumantik was 88.25%, while the respondents who had the PSN culture after being given leaflets were 42.51% Conclusion : The results showed that the use of the PSN reminder application was more effective in cultivating PSN on jumantik houses compared to the intervention in the form of leaflets.